PHARMACOLOGICAL POTENTIAL OF BOERHAAVIA DIFFUSA: AN OVERVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Ayurveda, the science of life, deals with the holistic view of healthy living. It covers various physiology and pathology of diseases and their therapies. From time immemorial mankind's efforts and ultimate aim have been to seek eternal happiness. And his endeavour has been to overcome and seek appropriate remedies for things that stand in his way. Physical and mental well being is of prime importance towards this end Medical Science while relieving his malady assures him of a healthy life man or living being for that matter is afflicted by grief or disease even since inception. Phytochemical, Pharmacological, experimental and Clinical investigations on various medicinal plants have been conducted by many scientist, researchers etc. It may be seen that the ancient Ayurvedic physicians clearly understood the process of digestion and metabolism. Boerhaavia diffusa (Punarnava) is one of the most famous medicinal plants in the treatment of a large number of human ailments is mentioned in Ayurveda, Charaka Samhita, and Sushrita Samhita. This paper explains the evidence-based information regarding the pharmacological activity of this plant. It has many ethnobotanical uses (the leaves are used as vegetable; the root juice is used to cure asthma, urinary disorders, leukorrhea, rheumatism, and encephalitis), and is medicinally used in the traditional Ayurvedic system.